Reformasi Syariat Islam (Kritik Pemikiran Khalīl ‘Abd al-Karīm) - Siti Mahmudah (Al 'Adalah: Jurnal Hukum Islam, 2017)
Abstract: Reformation of the  Sharia (Islamic Law): A Review  of  Khalīl 'Abd al-Karīm Thought) This article analyses the conflicting  views between Egyptian Islamists and Khalīl 'Abd al-Karīm on the entity of Shari'ah (Islamic Law). According to the Islamist group, Shari’ah is a pure devine law without any influence of whatsoever and from wheresoever.  It could even be used as an alternative to resist the exercises of secular and pro-Western power in Egypt. Khalīl 'Abd al-Karīm rejects this argument on the grounds that Islamic law is not pure as it also adopted pre-Islamic Arab tradition. According to Khalīl, the true Islamic Shari'a is the law born in Makkah and Madina in the presence of Arab communities bound to the traditions of ancestors. In fact, both Khalīl and the Islamists, have similar view that the true Islamic law is what had been  practiced by the Prophet Muhammad during his life in Mecca and Medina. Still, the two sides have grounded their interpretation differently; Islamists interpret the concept of Islamic law through textualist historical approach, while Khalīl interpret it through contextualist historical approach.